2009
DOI: 10.1002/pssa.200881282
|View full text |Cite
|
Sign up to set email alerts
|

UV emission on a Si substrate: Optical and structural properties of γ‐CuCl on Si grown using liquid phase epitaxy techniques

Abstract: Considerable research is being carried out in the area of wide band gap semiconductor materials for light emission in the 300–400 nm spectral range. Current materials being used for such devices are typically based on II–VI and III‐nitride compounds and variants thereof. However, one of the major obstacles to the successful fabrication of III‐N devices is lattice mismatch‐induced high dislocation densities for epitaxially grown layers on non‐native substrates. γ‐CuCl is a direct bandgap material and an ionic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…It has been previously reported that γ‐CuX (X = Br and Cl) have significant light emission properties in the 300–400 nm spectral range, suitable for novel UV/blue light applications . Here, we also measured the room temperature emission spectra of γ‐CuX (Figure S14, Supporting Information), that show a UV‐blue light emission with the presence of two PL peaks at 384 and 395 nm for γ‐CuCl and at 422 and 433 nm for γ‐CuBr, in agreement with the previous reports 22a,23. However, the measured PLQY values of γ‐CuX are very low (<0.5%).…”
supporting
confidence: 91%
“…It has been previously reported that γ‐CuX (X = Br and Cl) have significant light emission properties in the 300–400 nm spectral range, suitable for novel UV/blue light applications . Here, we also measured the room temperature emission spectra of γ‐CuX (Figure S14, Supporting Information), that show a UV‐blue light emission with the presence of two PL peaks at 384 and 395 nm for γ‐CuCl and at 422 and 433 nm for γ‐CuBr, in agreement with the previous reports 22a,23. However, the measured PLQY values of γ‐CuX are very low (<0.5%).…”
supporting
confidence: 91%
“…It is observed that the optical gain and the luminescence of cuprous halides CuI/CuCl and CuBr/CuCl QWs would be much higher than those of III-V nitride layers or II-VI ZnO/MgZnO QWs due to the inherent strong excitonic effects and negligible electrostatic fields within the active layers. Our predictions agree with recent experimental results 39 qualitatively. Substantially high optical gain of I-VII cuprous halides QWs as compared with that of III-V nitride QWs or II-VI ZnO QWs and the cuprous halides semiconductor structure’s close lattice match to Si substrate are the clear manifestation of the possibility of highly efficient I-VII cuprous halides semiconductor based light-emitting devices for solid-state lighting and integrated optoelectronic components compatible to Si technology.…”
supporting
confidence: 92%
“…Recently, I-VII γ -cuprous halides semiconductors 20 such as CuCl, CuBr, and CuI have drawn attention 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 because these are zincblende direct band-gap semiconductors (3.3 eV for CuCl, 2.91 eV for CuBr and 2.95 eV for CuI) and have large exciton binding energies (190 meV for CuCl, 108 meV for CuBr and 58 meV for CuI) with their lattice constants closely matched to that of Si as can be seen by the table 1 . From this table, one can see that the lattice constant of Si, 0.543 nm, is very closely matched to that of CuCl, 0.542 nm.…”
mentioning
confidence: 99%
See 2 more Smart Citations